2017
DOI: 10.18632/oncotarget.18687
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of stathmin plays a pivotal role in the metastasis of esophageal squamous cell carcinoma

Abstract: PurposeEsophageal squamous cell carcinoma (ESCC) is a serious malignant tumor that affects human health. We analyzed the correlation between serum stathmin level and ESCC and elucidated the molecular mechanisms of stathmin's promotion of ESCC cell invasion and metastasis.MethodsStathmin level in ESCC and healthy control serum were detected by enzyme-linked immunosorbent assay (ELISA), and the clinical parameters were analyzed. We established ESCC cells with stathmin overexpression or knockdown and then evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 54 publications
2
21
0
Order By: Relevance
“…It remains unknown whether serum stathmin‐1 can also reflect the malignant phenotype of tumor cells. Based on the very limited reports, including our own, serum stathmin‐1 levels have also been associated with advanced stage and lymph node metastasis in ESCC, lung cancer, and transitional cell carcinoma of the bladder . Therefore, circulating stathmin‐1 is also derived from oncogenic cells, and it is an ideal biomarker for liquid biopsy.…”
Section: Discussionmentioning
confidence: 95%
“…It remains unknown whether serum stathmin‐1 can also reflect the malignant phenotype of tumor cells. Based on the very limited reports, including our own, serum stathmin‐1 levels have also been associated with advanced stage and lymph node metastasis in ESCC, lung cancer, and transitional cell carcinoma of the bladder . Therefore, circulating stathmin‐1 is also derived from oncogenic cells, and it is an ideal biomarker for liquid biopsy.…”
Section: Discussionmentioning
confidence: 95%
“…Functionally, it has been found to modulate microtubule dynamics, cytoskeleton biogenesis, and focal adhesion reorganization, thus affecting cellular morphology and processes, such as angiogenesis, cell division, migration, and invasion . Recently, it has also been shown to be over‐expressed and associated with metastasis, cancer progression, and poor prognosis in several human malignancies . Similarly, we had reported earlier that STMN1 is a hallmark of CRC progression and predictor for poor survival, and that STMN1 silencing resulted in arrest of tumor‐disseminative cascades .…”
Section: Introductionmentioning
confidence: 54%
“…Regarding OP18, also termed oncoprotein 18 and stathmin-1, immunohistochemical analyses of human donors and studies in the bladder cancer cell line T24 indicated that over-expression of OP18 is related to malignant cell characteristics. It is noteworthy that the role of increased expression of OP18 for tumor development and metastatic growth seems to be true also for other tumor types including esophageal squamous cell carcinoma [20,21] and lung adenocarcinoma [22]. In summary, these studies warrant a closer look at OP18 transcripts as an RNA-based tumor marker in BCa.…”
Section: Introductionmentioning
confidence: 81%